Age and sex-specific changes in mitochondrial quality control in skeletal and cardiac muscle - Springer-Sapp, Catherine B.; Ogbara, Olayinka; Canellas Da Silva, Maria; Henderson, AbryAnna; Liu, Yuan; Prior, Steven J.; Kuzmiak-Glancy, Sarah (Frontiers in Aging, 2025)
IntroductionSkeletal and cardiac muscle mitochondria exist in a dynamic reticulum that is maintained by a balance of mitochondrial biogenesis, fusion, fission, and mitophagy. This balance is crucial for adequate ATP production, and alterations in skeletal muscle mitochondria have been implicated in aging-associated declines in mitochondrial function.MethodsWe sought to determine whether age and biological sex affect mitochondrial content [Complex IV (CIV)], biogenesis (PGC-1ɑ), fusion (MFN2, OPA1), fission (DRP1, FIS1), and mitophagy (Parkin, Pink1) markers in skeletal and cardiac muscle by assessing protein expression in tibialis anterior (TA) and ventricular tissue from 16 young (≤6 months) and 16 old (≥20 months) male and female Sprague-Dawley rats.ResultsIn the TA, CIV expression was 40% lower in old vs. young rats (p < 0.001), indicating lower mitochondrial content, and coincided with higher expression of Parkin (+4-fold, p < 0.001). Further, MFN2 expression was higher (+2-fold, p < 0.005) and DRP1 expression was lower (−40%, p = 0.014) in older rats. In cardiac muscle, mitochondrial content was maintained in old vs. young rats, and this occurred concomitantly with higher expression of both PGC-1ɑ and Parkin. MFN2 and OPA1 expression were also 1.2-5-fold higher in older rats (p < 0.05 for all). Largely, protein expression did not differ between male and female rats, with the exception of Pink1 and FIS1 expression in the TA.DiscussionCollectively, older skeletal and cardiac muscle demonstrated higher expression of fusion and mitophagy proteins, which indicates age alters the balance of biogenesis, fission, fusion, and mitophagy. This may, in turn, affect the ability to provide ATP to these metabolically active tissues.